Analysing the Role of Technological Innovation in Improving the Operational Efficiency of MSMEs - Bambang Triwahyono; Tri Rahayu; Kraugusteeliana Kraugusteeliana (Politeknik Ganesha Medan, 2023)
MSMEs play an important role in a country's economy. They are one of the pillars of the economy that contribute significantly to economic growth, job creation, and improving people's welfare. However, MSMEs often face various challenges, including limited human resources, capital, and adequate infrastructure. This study aims to analyse the role of technological innovation in improving the operational efficiency of MSMEs. The current research type is qualitative. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The study results state that technology plays a crucial role in facing various challenges faced by MSMEs. Technological innovation provides opportunities to improve production processes, inventory management, marketing, and customer reach. In addition, technology also facilitates more efficient financial management, internal operations, and data analysis. All these efforts can help MSMEs reduce operational costs, improve product and service quality, and enhance their competitiveness in the global market.